Learning and knowledge processes in an academic-management consulting research programme. The case of the MC Centre - Marcos Cuevas, Javier (Cranfield University, 2006)
The purpose of this thesis is twofold: to explore learning and knowledge processes in an academic-management consultancy collaborative research programme, and to investigate the enablers and barriers of these processes. The research is driven by an interest in understanding the nature of the divide between academic management research and management practice, the so called `relevance gap'. A narrative review of Organisational Learning theory is used to inform and ground the research. In addition, a systematic review on learning and knowledge processes within and across organisations is conducted. From the systematic review, a conceptual framework is derived to guide empirical work. This framework identifies three key classes of enablers and barriers to learning and knowledge processes: `content', `practices' and `people'. The research design consists of an in-depth, longitudinal single case study with five embedded units of analysis (research projects). The case is explored by means of participant observation, semi-structured interviews, repertory grids and document analysis over a period of five years (2001-2006). The study identifies a number of paradoxes at individual, group and organisational levels that affect learning and knowledge processes in this case. Among others, a lack of a clearly articulated purpose, unclear mechanisms to exploit research findings, and non-sustained engagement of people help to explain how learning and knowledge failed to occur in some research projects but thrived in others. Purposeful engagement is proposed as an overarching integrative theme to enhance learning and knowledge in academic-management consulting research programmes. This thesis contributes to theory providing a theoretically-informed, empirically¬grounded conceptualisation of enablers and barriers to learning and knowledge processes in academic-management consulting research programmes. This conceptualisation offers new perspectives to dimensionalise the divide between academic management research and management practice, contributing to the relevance gap debate. The thesis contributes to methodology by providing an exemplar of the adoption of an evidence-informed approach to knowledge using systematic review in the management field.